Predictive Factors for Gram-negative Versus Gram-positive Bloodstream Infections in Children With Cancer. Issue 2 (22nd March 2022) - Sfetsiori, Angeliki-Eleni; Doganis, Dimitrios; Doudoulakakis, Anastasios; Spyridis, Nikolaos; Pourtsidis, Apostolos; Servitzoglou, Marina; Nikita, Maria; Papachristidou, Smaragda; Magkou, Evgenia; Dana, Helen; Lebessi, Evangelia; Kosmidis, Helen; et al.
Abstract : Background: Identifying potential predictive factors for the type of bacteremia (Gram-negative vs. Gram-positive) in children with cancer would be crucial for the timely selection of the appropriate empiric antibiotic treatment. Materials and Methods: Demographic, clinical, and laboratory characteristics of children with cancer and a bacterial bloodstream infection (BSI) (February 1, 2011 to February 28, 2018) in a tertiary pediatric oncology department were retrospectively examined and were correlated with the type of isolated bacteria. Results: Among 224 monomicrobial bacterial BSI episodes, Gram-negative and Gram-positive bacteria were isolated in 110 and 114 episodes, respectively. Gram-negative bacteria were isolated significantly more frequently in girls (Gram-negative/Gram-positive ratio 1.7:1) versus boys (Gram-negative/Gram-positive ratio 0.72:1), P= 0.002, in patients with previous BSI episodes (1.4:1) versus those without (0.8:1), P =0.042, and in children with hematologic malignancy (1.3:1) versus those who suffered from solid tumors (0.52:1), P= 0.003. Gram-negative BSI episodes were more frequently correlated with a lower count of leukocytes, P= 0.009, neutrophils, P= 0.009 and platelets, P= 0.002, but with significantly higher C-reactive protein (CRP) levels, P= 0.049. Female sex, hematologic malignancy, and higher CRP levels remained independent risk factors for Gram-negative BSI in the multivariate analysis. Among neutropenic patients, boys with solid tumors and a recent central venous catheter placement appear to be at increased risk for Gram-positive BSI in the multivariate analysis. Conclusions: Although Gram-negative and Gram-positive BSIs are close to balance in children with cancer, Gram-negative bacteria are more likely to be isolated in girls, children with hematologic malignancies and those with higher CRP level at admission. In contrast, neutropenic boys with solid tumors and a recently placed central venous catheter may be at increased risk for Gram-positive BSI indicating probably the need for initially adding antibiotics targeting Gram-positive bacteria.